Trait Self-Control Discriminates Between Youth Football Players Selected and Not Selected for the German Talent Program: A Bayesian Analysis - Wolff, Wanja; Bertrams, Alex; Schüler, Julia (Frontiers in Psychology, 2019)
Trait self-control predicts success in various walks of life. Sports is a prototypical domain, where self-control is required, and there is evidence that successful athletes display superior self-control. Here, we assess if self-control already differs between athletes that were selected for a talent development program and non-selected athletes. Self-reported trait self-control was assessed in n = 25 (7 = female, 13.2 ± 1.7 years) youth football players who were part of the German talent development program and in n = 27 (6 = female, 13.6 ± 1.8 years) age and sex matched youth football players, who trained at the same clubs but had not been selected for the program. A one-sided Bayesian two-sample t-test yielded a Bayes factor of 54.99, indicating very strong evidence for the hypothesis that elite youth football players have higher trait self-control than non-elite youth football players. The 95% credibility interval for the two-sided t-test indicates that the true value of δ lies between 0.28 and 1.42, indicating some uncertainty regarding the effects’ magnitude. We show that already at young age, elite athletes display higher levels of self-control than their less successful peers. This underlines the importance of self-control as an important personality factor for success. These findings might have implications for talent selection and for sport psychological training.